2022
DOI: 10.3389/fpubh.2022.804031
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Total Cholesterol Variability on Clinical Outcomes After Percutaneous Coronary Intervention

Abstract: AimExploring the risk factors of prognosis in patients undergoing percutaneous coronary intervention (PCI) is of great importance. Our aim of the study is to investigate the association between variability in total cholesterol (TC) level and major adverse cardiovascular and cerebrovascular events (MACCE) in patients after PCI.MethodsBetween April 2004 and December 2009, 909 patients who underwent primary PCI and with at least three TC values were included in the final study. TC variability was calculated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…As is well known, TG, LDL-C, and HDL-C have different roles in the transport of cholesterol and different functions regarding atherogenesis and inflammation. Although the lack of detailed information on lipid fractions is one of the major limitations of this study, several previous studies have shown that total cholesterol variability is associated with the risk of vascular outcomes in patients after percutaneous coronary intervention, atrial fibrillation, end-stage renal disease, and dementia [ 15 , 18 , 43 , 44 , 45 ]. Second, the information about several medical conditions that can affect total cholesterol levels, including a history of familial hypercholesterolemia, and several well-known risk factors for osteoporotic fractures, including BMD values, vitamin-D levels, history of premature menopause, the use of medications such as glucocorticoids, and other endocrine or chronic inflammatory diseases, were not included in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As is well known, TG, LDL-C, and HDL-C have different roles in the transport of cholesterol and different functions regarding atherogenesis and inflammation. Although the lack of detailed information on lipid fractions is one of the major limitations of this study, several previous studies have shown that total cholesterol variability is associated with the risk of vascular outcomes in patients after percutaneous coronary intervention, atrial fibrillation, end-stage renal disease, and dementia [ 15 , 18 , 43 , 44 , 45 ]. Second, the information about several medical conditions that can affect total cholesterol levels, including a history of familial hypercholesterolemia, and several well-known risk factors for osteoporotic fractures, including BMD values, vitamin-D levels, history of premature menopause, the use of medications such as glucocorticoids, and other endocrine or chronic inflammatory diseases, were not included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Intraindividual variability of several biological measures, including blood pressure, heart rate, and glucose, could be a predictive biomarker of adverse health outcomes [ 11 ]. Visit-to-visit cholesterol variability has been found to act as a risk factor for cardiovascular diseases, stroke, and mortality regardless of the cholesterol target levels achieved to lower the risk [ 12 , 13 , 14 , 15 , 16 ]. Moreover, cholesterol variability has been found to be related to a risk of end-stage renal disease, lower cognitive performance, and even Parkinson’s disease [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The biggest risk factor for CAD is abnormal blood lipid metabolism. The risk is also greater with high total cholesterol concentration (Liang et al, 2022).…”
Section: Carbohydratementioning
confidence: 99%